A new species of the endemic South African spider genus Austrachelas (Araneae: Gallieniellidae) and first description of the male of A. bergi - Haddad, Charles R.; Mbo, Zingisile (Zootaxa, 2017)
The Gallieniellidae is a small family of ground-dwelling gnaphosoid spiders with a Gondwanan distribution, currently including 10 genera and 55 species (World Spider Catalog 2017). The composition of the group remains unresolved, as different phylogenies have either supported (Platnick 2002; Haddad et al. 2009) or disputed (Ramírez 2014; Wheeler et al. in press) its monophyly.